2019
DOI: 10.1108/s1745-354220190000015004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Grit in Enhancing Job Performance of Frontline Employees: The Moderating Role of Organizational Tenure

Abstract: This study investigates the role of grit in a work setting as well as interrelationships among work-related constructs among frontline employees of hotels. Based on the framework of grit and work-related constructs, this study proposes and tests a model that attempts to understand the dynamic relationship among the two dimensions of grit, customer orientation, job satisfaction, and job performance, with an emphasis on the moderating role of organizational tenure. The results indicate that consistency of intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 82 publications
3
22
0
1
Order By: Relevance
“…Grit is positioned as a vital personal resource required to translate individual drive and resolve, into measurable performance outcomes on both an individual and organizational level (Nelson and Baltes, 2019). Previous studies reported a direct and positive relationship between grit and various permutations of performance ranging from academic success/performance (Duckworth and Quinn, 2009;Jachimowicz et al, 2018;Nelson and Baltes, 2019), and training performance in sports (Cazayoux and DeBeliso, 2019), to job performance (Jordan et al, 2019;Kim et al, 2019;Webster-Wright, 2019), operational productivity (Steuber et al, 2019), and even task performance (Vogelsang, 2018). Koopmans et al (2013) argued that task performance seems to be an important indicator of operational efficiency and personal performance, which is also strongly influenced by non-cognitive traits such as personality, interest and drive.…”
Section: Concurrent Validitymentioning
confidence: 99%
“…Grit is positioned as a vital personal resource required to translate individual drive and resolve, into measurable performance outcomes on both an individual and organizational level (Nelson and Baltes, 2019). Previous studies reported a direct and positive relationship between grit and various permutations of performance ranging from academic success/performance (Duckworth and Quinn, 2009;Jachimowicz et al, 2018;Nelson and Baltes, 2019), and training performance in sports (Cazayoux and DeBeliso, 2019), to job performance (Jordan et al, 2019;Kim et al, 2019;Webster-Wright, 2019), operational productivity (Steuber et al, 2019), and even task performance (Vogelsang, 2018). Koopmans et al (2013) argued that task performance seems to be an important indicator of operational efficiency and personal performance, which is also strongly influenced by non-cognitive traits such as personality, interest and drive.…”
Section: Concurrent Validitymentioning
confidence: 99%
“…However, prior research in the human resources management fields has found the significant moderating role of organizational tenure (i.e. years of work experience) in the paths from frontline employees’ perceptions to their behaviors in the workplace (Kim et al , 2019). In addition, the study of Kim et al (2016) found that the generation difference was a significant moderator in the relationship between employee motivation and pro-environmental behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological capability of the FLEs is associated with their passion to derive benefits to the organizations by sincerely discharging their duties towards the potential customers of the organizations ( Kim et al, 2019 ). Passion is considered as a motivational force emerging from the psychological alignment of the FLEs which drives the FLEs to work sincerely for the benefits of the organizations ( Sadeghi, & Fekjaer, 2019 ).…”
Section: Theoretical Underpinning and Development Of Conceptual Modelmentioning
confidence: 99%
“… [1–5] EIC6 Mehmood et al, 2020 I believe that emotional intelligence helps in improving adaptability of the frontline employees. [1–5] PCA1 Kim et al, 2019 I believe that psychological capability of frontline employees is an asset of the organization. [1–5] PCA2 Sadeghi, & Fekjaer, 2019 I think that psychological capability of frontline employees is related to dynamic capability of the organization.…”
Section: Summary Of Questionnairementioning
confidence: 99%